Advanced Imaging of Type 2 Spinal CSF Leaks with Ultra-High-Resolution Conebeam CT Myelography - Lützen, Niklas; Zander, Charlotte; Beck, Jürgen; Volz, Florian; Wolf, Katharina; El Rahal, Amir; Urbach, Horst (American Journal of Neuroradiology, 2025)
Type 2 CSF leaks are spinal lateral dural tears, causing spontaneous intracranial hypotension. They may be visualized with digital subtraction myelography, conebeam CT myelography, and energy-integrating detector or photon-counting CT myelography. A recently introduced ultra-high-resolution conebeam CT myelography has shown beneficial visualization of CSF-venous fistulas, another cause of spontaneous intracranial hypotension. However, the use of this technique has not yet been reported in imaging of type 2 leaks. In this technical report, we describe our first experiences and highlight the advantages of ultra-high-resolution conebeam CT for visualizing type 2 leaks in spontaneous intracranial hypotension.CBCTconebeam CTDSMdigital subtraction myelographySIHspontaneous intracranial hypotensionUHR-CBCTultra-high-resolution conebeam CT